Lecture Notes Clinical Biochemistry - Beckett, Geoffrey Walker, Simon Rae, Peter (Blackwell Publishing, 2005)
"Lecture Notes: Clinical Biochemistry lakes a system-based approach. The underlying physiological rationale for any test is explained in the context of disruption by disease. This leads naturally to an integrated and practical understanding of chemical diagnostics. Case studies at the end of each chapter provide a clinical setting to help develop test-selection skills. Lecture Notes: Clinical Biochemistry provides the essential background to chemical investigations for medical students, junior doctors on foundation programmes, and nurses and practitioners involved in requesting or providing diagnostic services."--Jacket.